1998
DOI: 10.1161/01.atv.18.10.1589
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Metabolism and Efflux in Human THP-1 Macrophages

Abstract: Abstract-This study has investigated in detail factors regulating accumulation, esterification, and mobilization of cholesterol in human THP-1 macrophages. Human THP-1 monocytes were differentiated into macrophages and then cholesterol enriched by exposure to acetylated LDL (AcLDL), together with [ 3 H]free cholesterol (FC). Although THP-1 macrophages accumulated FC and esterified cholesterol (EC), assessed by both mass and radioactivity, cellular EC always demonstrated a much lower specific activity (cpm/g) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
94
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 60 publications
(45 reference statements)
7
94
1
Order By: Relevance
“…Cells were plated in 12-well tissue culture plates (Falcon) at a density of 1.5 ϫ 10 6 cells per ml of RPMI medium containing 10% heat-inactivated human serum and left to adhere and differentiate into macrophages (hMDM) over the next 10 days. Subsequently, cells were washed and incubated in RPMI medium containing 10% lipoprotein-depleted serum in the presence of 100 g/ml acetylated LDL (acLDL) for 48 h to generate lipid-laden "foam cells" as described (28). For metabolic labeling of cellular cholesterol pools, acLDL was first labeled with [ 3 H]cholesterol (51 Ci/mmol, Amersham Pharmacia Biotech) for 6 h (28), before [ 3 H]cholesterol-acLDL was diluted in RPMI (100 g/ml acLDL and 2 Ci/ml [ 3 H]cholesterol), and then incubated with cells.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were plated in 12-well tissue culture plates (Falcon) at a density of 1.5 ϫ 10 6 cells per ml of RPMI medium containing 10% heat-inactivated human serum and left to adhere and differentiate into macrophages (hMDM) over the next 10 days. Subsequently, cells were washed and incubated in RPMI medium containing 10% lipoprotein-depleted serum in the presence of 100 g/ml acetylated LDL (acLDL) for 48 h to generate lipid-laden "foam cells" as described (28). For metabolic labeling of cellular cholesterol pools, acLDL was first labeled with [ 3 H]cholesterol (51 Ci/mmol, Amersham Pharmacia Biotech) for 6 h (28), before [ 3 H]cholesterol-acLDL was diluted in RPMI (100 g/ml acLDL and 2 Ci/ml [ 3 H]cholesterol), and then incubated with cells.…”
Section: Methodsmentioning
confidence: 99%
“…Human monocytes ( Ͼ 95% pure by nonspecific esterase staining) were isolated by centrifugal elutriation from fresh white blood cell concentrates and plated at 1.5-2.0 ϫ 10 6 cells per 22 mm-diameter culture dish in RPMI-1640 media containing penicillin and streptomycin (50 U/ml and 50 g/ml, respectively) at 37 Њ C as described (14,32,33). Monocytes were incubated for an initial 1.5 h to establish adherence, and then the medium was exchanged with fresh RPMI-1640-containing 10% heat-inactivated whole human serum.…”
Section: Culture and Loading Of Cellsmentioning
confidence: 99%
“…Data from several laboratories indicate that human macrophages are resistant to cholesterol efflux, at least in part due to slow mobilization of stored CEs by hydrolysis (12)(13)(14). In addition, as the flux of cholesterol through all cellular compartments is slow in human THP-1 macrophages (14), factors other than CE hydrolysis may also be limiting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was a significant increase in CE deposition in our THP-1 cells, the major neutral lipid accumulated was TG. In this connection it may be noted that recent studies have shown that THP-1 cells contain a large and metabolically active TG pool but a relatively inactive pool of CE (26). A large and active TG pool has also been seen in other human macrophage cultures, but the regulation of TG metabolism in these cells is not known.…”
Section: Figmentioning
confidence: 97%